Fragmentación, vida y humor en Disonante - Lescano Tena, Miguel (2019)
The book Disonante shows that text and image are both important for communicative language. The relationship between both joins fragmented ideas and contrasts between verbal and visual poetics. Disonante reveals an hermetic world where the self portrays an ironic view about society. Its goal is to get a performative approach between life and art. Its aim is for the receptor to extend his imagination towards new worlds, without leaving this reality of dreams and nightmares shaped in white and black.